Structural mechanism of JH delivery in hemolymph by JHBP of silkworm, Bombyx mori - Suzuki, Rintaro (Nature Publishing Group, 2011)
Juvenile hormone (JH) plays crucial roles in many aspects of the insect life. All the JH actions are initiated by transport of JH in the hemolymph as a complex with JH-binding protein (JHBP) to target tissues. Here, we report structural mechanism of JH delivery by JHBP based upon the crystal and solution structures of apo and JH-bound JHBP. In solution, apo-JHBP exists in equilibrium of multiple conformations with different orientations of the gate helix for the hormone-binding pocket ranging from closed to open forms. JH-binding to the gate-open form results in the fully closed JHBP-JH complex structure where the bound JH is completely buried inside the protein. JH-bound JHBP opens the gate helix to release the bound hormone likely by sensing the less polar environment at the membrane surface of target cells. This is the first report that provides structural insight into JH signaling.